Efficiency of public investment spending and its impact on economic growth in Iraq For the period 2003- 2013 - داود, سمير سهام; جري, وديان وهيب (Journal of Economics and Administrative Sciences, 2017)
Occupy public investment spending, a great deal of attention since the thirties of the last century, to play important role in economic and social development process and therefore most of the countries are trying different degree of economic development to the completion of the largest amount of public investment, especially in infrastructure, which is one of the pillars essential to economic development, and in order to maximize utilization of the completion of public investment should focus on achieving efficiency in completion.     The current reality of public projects in Iraq, indicating the absence of several key characteristics that must be provided if these projects to achieve high efficiency performance. The results achieved by these projects less than ambitions that could have been achieved, if we take into account the size of allocations and opportunities for these projects, and thus had a negative impact on achieving real growth in the gross domestic product, as it is because the reason for the low levels of implementation to the low level of implementation of public projects on the one hand, and the weakness of oversight bodies on the other.    In order to measure the efficiency of public investment spending in Iraq will be selected two indicators, one applicable index in some developed countries in the world, which depends on measurement of the efficiency of the qualitative side, an indicator (diagnostic tests), while the second indicator, it is practice Index by the Iraqi Ministry of Planning , a quantitative index depends on the achievement of financial ratios public projects account, due to the breadth of public investment spending, it has been chosen the electricity sector to be a case study, to demonstrate the level of efficiency in the implementation of public projects.After subjecting the electricity sector to measure efficiency, notes the low level of efficiency of implementation, the electricity sector deficit in the implementation of all of them as a result of the low efficiency of the implementation, and the financial and administrative corruption and the lag in the completion of projects had a direct and significant reason for the lack of implementation of many projects and this is illustrated low percentage of completion in most projects of this sector, but for the most important recommendation graduated by the study is the work on the adoption of new efficiency indicators complement indicators currently used to measure efficiency in many ways, in order to stand on the level of implementation of projects more clearly, and thus to identify the most important the reasons for winning the lag in the implementation process in order to improve the implementation  of these vital projects